Perancangan Arsitektur Enterprise Orkestrasi Cloud Berbasis Togaf Pada PT. XYZ - Miqdad Zaidan Alkhair Alkhair; Roso Sasongko; Kursehi Falgenti; Supyan Haryanto; Windu Setiawan (LPPM Universitas Putera Batam, 2026)
The rapid adoption of cloud computing in enterprise environments introduces challenges related to infrastructure governance, security, scalability, and deployment consistency. PT XYZ, as a technology-driven organization, faces limitations in managing cloud infrastructure due to manual provisioning, fragmented access control, and the absence of a standardized architectural blueprint. This study aims to design an enterprise architecture for cloud infrastructure orchestration using The Open Group Architecture Framework (TOGAF). The research adopts a qualitative approach, utilizing document analysis and architectural modeling techniques. The TOGAF Architecture Development Method (ADM) is applied to analyze the existing architecture (As-Is) and design the target architecture (To-Be). The proposed architecture emphasizes Infrastructure as a Service (IaaS) supported by Amazon Web Services (AWS), with Amazon Elastic Kubernetes Service (EKS) as the core orchestration platform for application deployment. The resulting enterprise architecture consists of business, application, and technology architectures, modeled using IDEF0 and ArchiMate. The findings demonstrate that the proposed architecture improves infrastructure standardization, enhances deployment automation, strengthens security governance, and supports scalability. This study contributes an architectural blueprint that can be utilized as a reference for cloud-based enterprise architecture implementation in similar organizations.